The integrated use of scenario planning in strategic management by South African-based multinational companies. - Nel, Coenrad Marais (My University, 2014)
ABSTRACT Dealing with the uncertainties of the global business environment has become a challenge for companies. This is especially the case for multinational companies operating in a number of geographical areas, each having their driving forces and uncertainties to consider during the strategic planning process of the company. Increased global uncertainty led to companies understanding the importance of identifying and mitigating against these uncertainties. This research report aims to establish whether multinational companies based in South Africa utilise scenario planning as an integral part of their strategic management framework. The research was conducted in the form of interviews with thirty (30) respondents from multinational companies based in South Africa, consisting of ten (10) open-ended questions to gain an understanding of whether each company has a formal strategic management framework in place; to understand what the process of this framework involves, as well as to ascertain whether scenario planning forms an integral part of this framework. The analysis of the interview data established that all the respondents identify the importance of dealing with uncertainties in their business environments. The majority of the respondents utilise the PESTLE and Porter’s Five Forces models to identify uncertainties within the external and internal business environment of the companies. The companies further rely on external experts such as economists to assist them with understanding current and emerging trends within the global, regional and local business environments. Respondents also rely on their risk management processes and sensitivity analyses of their financial plans in an attempt to understand and mitigate against uncertainties. The research established that only three (3) of the thirty (30) respondents use scenario planning as an integral part of their strategic management framework. The research report therefore concluded that multinational companies based in South Africa do not utilise scenario planning as an integral part of their strategic management framework.
MBA Thesis 2011
Keywords: International business enterprises, Strategic planning .